Associations between one-carbon metabolism and valproic acid-induced liver dysfunction in epileptic patients - Zhu, Jingwei; Wang, Zhe; Sun, Xiaotong; Wang, Dan; Xu, Xinbo; Yang, Liping; Du, Jiangdong; Zhou, Zhimei; Qi, Yanhua; Ma, Linfeng (Frontiers in Pharmacology, 2024)
Valproic acid (VPA) has been widely used as an antiepileptic drug for decades.Although VPA is effective and well-tolerated, long-term VPA treatment is usually associated with hepatotoxicity. However, the underlying mechanisms of VPA-caused hepatotoxicity remain unclear. In this study, a total of 157 pediatric patients with epilepsy were recruited and divided into normal liver function (NLF, 112 subjects) group and abnormal liver function (ABLF, 45 subjects) group. We observed that MTHFR A1298C and MTHFR C677T variants may be linked to VPA-induced liver dysfunction (P = 0.001; P = 0.023, respectively). We also found that the MTHFR A1298C polymorphism was associated with a higher serum Hcy level (P = 0.001) and a lower FA level (P = 0.001). Moreover, the serum Hcy levels was strongly correlated with the GSH and TBARS concentrations (r = -0.6065, P ˂ 0.001; r = 0.6564, P ˂ 0.001, respectively). Furthermore, logistic analysis indicated that MTHFR A1298C/C677T polymorphisms and increased Hcy concentrations may be risk factors for VPA-induced liver dysfunction. These results suggested that individual susceptibility to VPA-induced liver dysfunction may result from MTHFR A1298C/C677T polymorphisms and increased Hcy levels. This study may be helpful for the prevention and guidance of VPA-induced liver dysfunction.